Genetic inactivation of AKT1, AKT2, and PDPK1 in human colorectal cancer cells clarifies their roles in tumor growth regulation - Ericson, Kajsa (National Academy of Sciences, 2010)
Phosphotidylinositol-3-kinase (PI3K) signaling is altered in the majority of human cancers. To gain insight into the roles of members of this pathway in growth regulation, we inactivated AKT1, AKT2, or PDPK1 genes by targeted homologous recombination in human colon cancer cell lines. Knockout of either AKT1 or AKT2 had minimum effects on cell growth or downstream signaling. In contrast, knockout of both AKT1 and AKT2 resulted in markedly reduced proliferation in vitro when growth factors were limiting and severely affected experimental metastasis in mice. Unexpectedly, AKT1 and AKT2 appeared to regulate growth through FOXO proteins, but not through either GSK3β or mTOR. In contrast, inactivation of PDPK1 affected GSK3β and mTOR activation. These findings show that the PI3K signaling pathway is wired differently in human cancer cells than in other cell types or organisms, which has important implications for the design and testing of drugs that target this pathway.